2016
DOI: 10.3389/fnhum.2016.00424
|View full text |Cite
|
Sign up to set email alerts
|

MAOA Influences the Trajectory of Attentional Development

Abstract: Attention is vital to success in all aspects of life (Meck and Benson, 2002; Erickson et al., 2015), hence it is important to identify biomarkers of later attentional problems early enough to intervene. Our objective was to determine if any of 11 genes (APOE, BDNF, HTR4, CHRNA4, COMT, DRD4, IGF2, MAOA, SLC5A7, SLC6A3, and SNAP25) predicted the trajectory of attentional development within the same group of children between infancy and childhood. We recruited follow up participants from children who participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 161 publications
(162 reference statements)
0
3
0
Order By: Relevance
“…Regarding rs1137070, it has been shown that the T variant is associated with higher activity than that of the C allele [50]. Moreover, it is considered a useful biomarker of attentional problems; in this regard, the study by Lundwall et al showed that this SNP predicted poorer developmental course in reaction time (RT) and that in girls, the carrier of CC genotype led to an increase in RT on a reflexive attention task between infancy and childhood [53].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding rs1137070, it has been shown that the T variant is associated with higher activity than that of the C allele [50]. Moreover, it is considered a useful biomarker of attentional problems; in this regard, the study by Lundwall et al showed that this SNP predicted poorer developmental course in reaction time (RT) and that in girls, the carrier of CC genotype led to an increase in RT on a reflexive attention task between infancy and childhood [53].…”
Section: Discussionmentioning
confidence: 99%
“…In the current context, impulsivity and approach tendency thus seem to be related to the MAOA polymorphism independently and are thereby a possible separate factor as suggested in model of gene‐environment interactions [Holz et al, ]. The genetic variation may influence other personality traits as well or bias learning and attention [Lundwall and Rasmussen, ; Ma et al, ] which in turn might lead to differential decision strategies in MAOA‐L or MAOA‐S carriers [Frydman et al, ]. Nevertheless, one of the most famous findings in research on the MAOA polymorphism is its known interaction with the environment [Beitchman et al, ; Meyer‐Lindenberg et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, they found IOR beginning at 360 and 780 ms in older children (11–17 years old) for tasks in which attention is drawn back to center prior to target presentation and at 570 ms when attention can remain at a cue location prior to target presentation. However, only a few studies examine how reflexive attention functions in school-age children ( Pearson and Lane, 1990 ; Brodeur and Boden, 2000 ; Wainwright and Bryson, 2002 ; Ristic and Enns, 2015 ; Lundwall and Rasmussen, 2016 ; Lundwall et al, 2017 ). In fact, we could find no study (besides our own) in our university library databases (e.g., PsycINFO, Academic Search Premier, MEDLINE) that used typically developing children, a peripheral cueing task, and both valid and invalid cues appearing at chance (50% for two locations).…”
Section: Introductionmentioning
confidence: 99%